(untitled) (Scholars’ Journal, 2020)
Teaching English has shifted from teaching literature to teaching language in cultural contexts. Teaching English in a cultural context improves intercultural competence but also needs to incorporate the local culture of the learners to enhance awareness and eliminate ethnocentricism. Intercultural approach tries to develop intercultural competence in the learners. Intercultural competence means following one’s own culture and respecting others’ cultural viewpoints. I have used phenomenological research design to find out perceptions of EFL teachers towards using intercultural approach in English language teaching. The finding indicates the need of practicing intercultural approach in English language teaching though the implementation is not quite easy. This research has also indicated that there is the hegemony of western culture in the course development and content selection. Still there are many problems in promoting local cultures and developing intercultural competence. To implement intercultural approach successfully, there should be radical changes in policy level, practice level, and pedagogical level, for the policy making, course development, content selection, classroom delivery and even in evaluation scheme.